2012
DOI: 10.1155/2012/316013
|View full text |Cite
|
Sign up to set email alerts
|

Are Pyogenic Liver Abscesses Still a Surgical Concern? A Western Experience

Abstract: Backgrounds. Pyogenic liver abscess is a rare disease whose management has shifted toward greater use of percutaneous drainage. Surgery still plays a role in treatment, but its indications are not clear. Method. We conducted a retrospective study of pyogenic abscess cases admitted to our university hospital between 1999 and 2010 and assessed the factors potentially associated with surgical treatment versus medical treatment alone. Results. In total, 103 liver abscess patients were treated at our center. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 27 publications
(59 reference statements)
5
59
1
Order By: Relevance
“…Thirty six percent patients had nausea and or vomiting ( Figure No.01). Our study result is similar to study by Barbara Alkofer and his colleagues [15]. But other study results are different.…”
Section: Discussionsupporting
confidence: 88%
“…Thirty six percent patients had nausea and or vomiting ( Figure No.01). Our study result is similar to study by Barbara Alkofer and his colleagues [15]. But other study results are different.…”
Section: Discussionsupporting
confidence: 88%
“…In recent years, a more conservative approach has been adopted and needle aspiration or percutaneous continuous catheter drainage in combination with parenteral antibiotics is considered the gold standard treatment [1,4,13,20,21] . The most commonly used antibiotics were fluoroquinolones, the third-generation cephalosporins with metronidazole and an aminoglycoside [4,19,22] .…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al found that intermittent needle aspiration was probably as effective as continuous catheter drainage for the treatment of PLA [25] . It's indicated in following situations [4,19] : (1) Patients who continued to be febrile even after 48-72 h of adequate medical treatment; (2) Liver abscess more than 6 cm in size; (3) Clinical or ultrasonographic features suggesting impending perforation. disseminate and in the other case the abscess was associated with a cholecystitis).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations